A Comprehensive Review of Tuberculosis: Epidemiology, Diagnosis, Treatment, Prevention, and Research - Mr. Rajesh Kumar; Sonam Sharma (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Tuberculosis (TB), which is triggered by Mycobacterium tuberculosis, continues to be a prominent contributor to infectious disease-related deaths worldwide, even after many years of attempts to manage it. Exceeding 10 million instances and surpassing a million fatalities each year, tuberculosis predominantly impacts nations with low to middle income. This is fuelled by elements like poverty, dense living conditions, inadequate nutrition, and co-infection with HIV. The rise of multidrug-resistant and extensively drug-resistant tuberculosis has added complexity to control measures. This evaluation delves into the comprehensive range of tuberculosis—covering aspects such as transmission, pathogenesis, worldwide epidemiology, diagnostic methods, treatment protocols, drug resistance, preventive measures, and current research endeavours. Focus is directed towards innovative molecular diagnostics, the incorporation of artificial intelligence, therapies aimed at the host, and the relationship between tuberculosis and comorbid conditions such as HIV and diabetes. An approach that encompasses multiple sectors and is fuelled by innovation is essential for achieving worldwide tuberculosis elimination goals.
Keywords: Tuberculosis; MDR-TB; Diagnosis; Host-Directed Therapies; Epidemiology; BCG Vaccine; Drug Resistance